2002
DOI: 10.1038/sj.ijir.3900893
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of erectile dysfunction in Colombia, Ecuador, and Venezuela: a population-based study (DENSA)

Abstract: The purpose of this study was to estimate the prevalence of erectile dysfunction (ED) in Colombia, Ecuador, and Venezuela. A 49-item questionnaire was completed by 1946 men aged 40 years and older. The age-adjusted combined prevalence of minimal, moderate, and complete ED for all three countries was 53.4%, with 19.8% of all men reporting moderate to complete ED. Age was the variable most strongly linked to ED; the prevalence of complete ED increased markedly in men older than 79 y of age (31.9%) and 70 -79 y (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0
24

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 7 publications
4
44
0
24
Order By: Relevance
“…The most common concomitant illnesses were hypertension and diabetes mellitus, with the most common concomitant medications being antihypertensive drugs and antidiabetic drugs. This observation is consistent with the identification of hypertension and diabetes and associated drug treatments as significant correlates of ED in the epidemiological studies conducted in Brazil 8 and the northern countries of South America (Colombia, Ecuador, Venezuela), 6 as well as in other epidemiological studies. 9 Consistent with the identification of vascular disease as a risk factor for ED, 10 approximately 7% of all patients had underlying ischemic heart disease.…”
Section: Concomitant Medical Conditions and Medicationssupporting
confidence: 74%
See 2 more Smart Citations
“…The most common concomitant illnesses were hypertension and diabetes mellitus, with the most common concomitant medications being antihypertensive drugs and antidiabetic drugs. This observation is consistent with the identification of hypertension and diabetes and associated drug treatments as significant correlates of ED in the epidemiological studies conducted in Brazil 8 and the northern countries of South America (Colombia, Ecuador, Venezuela), 6 as well as in other epidemiological studies. 9 Consistent with the identification of vascular disease as a risk factor for ED, 10 approximately 7% of all patients had underlying ischemic heart disease.…”
Section: Concomitant Medical Conditions and Medicationssupporting
confidence: 74%
“…This history is consistent with the finding of disorders of the prostate as well as prostatic surgery as risk factors for ED among the sample populations from Brazil 8 and Colombia= Ecuador=Venezuela. 6 A past or present history of depression (current depression is shown in Table 2), a common comorbid condition and risk factor among middle-aged and elderly men with ED, 9 was documented in eight patients in the sildenafil group (2.9%) and seven in the placebo group (2.6%), with 17 (3%) of the total study patients taking antidepressant drugs concomitantly.…”
Section: Concomitant Medical Conditions and Medicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,8 ED is the most common sexual dysfunction among men aged above 40 years and its prevalence is between 41.7 and 53.4% in different countries of America. 2,3,5,9,10 In Europe, a study of 2869 Austrian men found a prevalence of 32.2% (all degrees of severity). 11 In Finland in 3787 men aged 50-75 years, the prevalence of ED was 76.5%.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence was distributed by severity as follows: 33.6%, minimal ED; 16.2%, moderate ED; 3.6%, severe ED. 9 Currently recommended therapies for ED are limited and include intracorporal injection of vasoactive substances alone or in combination (papaverine, phentolamine, prostaglandin E1), 10 transurethral delivery of alprostadil, 11 vacuum devices, and prosthetic implantation. 12 All are associated with considerable limitations, including inconvenience, lack of spontaneity, poor toleration, and partial or restricted efficacy.…”
Section: Introductionmentioning
confidence: 99%